Risk of Zoonoses among Livestock Farmers in Nepal - Adhikari, Ramesh; Bagale, Kosh Bilash (Journal of Health Promotion, 2019)
In Nepal most of the people are engaged in agriculture and livestock farming but having low knowledge and poor practices are making them prone to zoo noses threats. The aim of this study is to identify the risk of common zoo noses and existing knowledge, practices among livestock farmer in Nepal and all over the world. The study was conducted based on literature review. Literature search from Google Scholar, Pub Med and Hinari databases was used for the study. The study shows that farmers have low knowledge and risky practices related to zoo noses. Sixty-five percent (n=40) of pork handlers were not following safety. Thirty six percent cattle farmers used to dispose placenta, 39.65% of them aborted foetus. Similarly, 23.25% farmers gave intra uterine medication with bare hands and 30% were sleeping in animal shed (n=250). African and South East Asian countries are facing more burden of zoo noses. Due to global warming and climate change, different zoo noses are emerging and re-emerging presentation in the world. Different research findings suggest that "One Health Approach" might help to fight against the zoo noses all over the world.